Book Reviews (Verbum et ecclesia, 2001)
Braaten, C E & Jenson, R W, 2000. Sin, death and the devil. Grand Rapids: Eerdmans. Prys: Onbekend. Michael Green, The Message of Matthew. Intervarsity Press, Leicester, 343 pp. Price £9.99. Francisco Lozada (Jr.), A literary reading of John 5. Text as construction. Peter Lang: New York, 138 pp. Price unknown. McGrath A & Packer JI (series eds), Thomas Manton, Jude 1999 [1675] 223 pp. John Calvin, 1 & 2 Timothy & Titus 1998 [1556] 208pp. John Owen, Hebrews 1998 [1680?] 269pp. The Crossway Classic Commentaries.